The Impact Of Entrepreneurial Orientation On The Profitability Of Banks Listed On The Damascus Parallel Stock Exchange - نادر, نهاد; حسون, عتاب; قاضي, زينب (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to analyze the impact of entrepreneurial orientation on the Profitability of banks, by studying seven dimensions of entrepreneurship which are(risk-taking, pro-activeness, innovations, competitive aggressiveness, autonomy, market orientation and environment).The research was based on the descriptive and analytical approach, whereby an electronic questionnaire was designed directed to the study sample, which is the Arab Bank, the bank of Syria and the Gulf, and the Bank of Jordan. It reached 239 items, with the aim of measuring their estimate of the impact of the entrepreneurial orientation. The researcher used multiple linear regression and SPSS program to analyze the data. The results showed that each of (competitive aggressiveness, rival- orientation, environment) has a positive and significant impact on Profitability of banks, meanwhile, for autonomy had a negative effect on the Profitability of banks. In contrast, we found that (risk-taking, pro-activeness, innovations and customer-orientation) had no significant impact on Profitability of banks.